Reformasi dalam Bayang Kemunduran Demokrasi? Analisis Tahun Pertama Kepemimpinan Prabowo Subianto - Fachirah, Dhia; Nurmiyati, Niken (JPP (Jurnal Politik Profetik), 2026)
This article examines the democratic backsliding in Indonesia by analysing the consolidation of execu-tive power during the first year of Prabowo Subianto’s administration. Using the democratic backslid-ing framework proposed by Haggard and Kaufman, this study focuses on three analytical dimensions: protection of freedoms, horizontal checks and balances, and elections. Using a qualitative process-tracing methodology, this article traces the institutional changes, elite strategies and legal interven-tions that have reshaped Indonesia’s democratic landscape. The findings indicate that democratic backsliding in Indonesia has not occurred through the dismantling of formal democratic institutions, but rather through the gradual repurposing of institutional functions to stabilise executive dominance while maintaining procedural legitimacy. This continuity across successive administrations suggests that Indonesia is moving toward a form of procedural democracy with declining substantive quality, highlighting the structural limitations of electoral competition in constraining executive power.